The impact of gender diversity in the boardroom on banks performances - Siti Farhana (Jurnal Keuangan dan Perbankan, 2020)
This research examined the impact of gender diversity in the boardroom on firm performance using banks listed on the Indonesia Stock Exchange (IDX) in the period from 2011 to 2016. Indonesia listed companies have a two-tier board structure that consist of management and supervisory board. In addition, listed companies should establish a committee board that consists of independent directors from outside the company. Thus, we investigate the gender diversity from each boardroom namely management, supervisory, and committee board. Gender diversity is measured by the Blau Index while bank’s financial performances are proxied by the Return on Assets (ROA) and Capital Adequacy Ratio (CAR). These two measurements are required by Indonesian Financial Service Authority or Otoritas Jasa Keuangan (OJK). We find that the average proportion of female directors sitting on management, supervisory, and committee board in banks are 16 percent, 9.7 percent, and 14 percent, respectively. Applying panel data analysis with fixed and random effect estimator and also addressing endogeneity issue, we find that there is no significant relationship between gender diversity indexes in each boardroom and both bank’s financial performance ROA and CAR. These findings may shed a light for regulator in Indonesia especially OJK whether they consider imposing gender quota in the boardroom. JEL Classification: G20, M41, M48DOI: https://doi.org/10.26905/jkdp.v24i4.4676